Taxonomia e distribuição geográfica das subespécies brasileiras de Erythrolamprus aesculapii (Linnaeus, 1758) (Serpentes, Colubridae) - Vasconcellos, Luís Roberto Silveira da Cunha (1998)
Populations of Erythrolamprus aesculapii from different Brazilian morfoclimatic domains were analyzed to carry out a taxonomic review. At present, three subspecies of E. aesculapii are recognized in Brazil. Scales counting and number of body rings were studied with analysis of variance. Patterns of coloration were classified and a sample of hemipenis were observed. Five basic patterns of coloration were recognized. The hemipenis of the specimens from different areas were virtually without differences, but the statistical analysis have discriminated the populations of E. aesculapii from Amazonian Equatorial Domain from the populations of others domains of Brazil, at least in relation of patterns of coloration, number of body rings and ventral scales counting.